A Survey on Weed Detection Using Image Processing in Agriculture - Choudhary, Jatin; Nayak, Sutapa (International Journal of Computer Sciences and Engineering, 2025)
Agriculture is one of the most important origins of human sustenance in whole world. Due to increasing population peoples require more productive capacity of the agriculture to fulfill the demands at present. In the past, we used natural methods to grow the productivity, such as using the cow dung as a fertilizer in the farms. That resulted in grow in the productivity according to demand of the population. But later we thought of growing more profits by getting more result. Therefore, there came a revolution named “Green Revolution”. After this period demand of dangerous poisons like herbicides has increased beyond limit. By getting so people got result in growing the productivity but people have ignored the side effects spread to the Eco system, which will raise suspense in our sustenance on this dangerous environment. So, in this research, we have tried to implement some techniques or methods to decrease the usage of herbicides by using them only in the geographical areas where weed available and destroying the crops. In this paper, we have used image processing using MATLAB to identify the weed place in an image which has been taken from the fields.